EFA Initiatives and the Barriers to Educating Girls and Young Women in Tanzania: A Rights-Based Approach - Bhalalusesa, Eustella Peter (Papers in Education and Development, 2018)
This paper adopts a rights-based approach to analysing the predicament which Tanzania has been facing in its effort to fulfil the international and national obligation to safeguard the universal right to education for its entire citizenry, particularly for girls and women. The paper makes reference to various policy documents that directly and indirectly relate to the right to education-for-all in Tanzania and uses them as a framework for analysis. The main argument of this paper is that although Tanzania has signed and ratified international instruments on the right to education and translated them into the national constitution and internal education policies, much is still needed to be done. Currently girls ' and women ' s right to education is still being inadequately addressed. While it is true that there has been no deliberate effort to deny women access to education, there certainly exist some structural problems as well as some prejudice resulting from the social, economic and cultural set-up of our communities, which continue to put girls and women at a disadvantage. Thus the government needs to create an enabling environment and demonstrate this in concrete activities before women and girls realise and enjoy their inalienable right to education.